Anacroneuria pakaraima and A. wokomung, two new stonefly species from Guyana (Plecoptera: Perlidae) - Stark, Bill P. (Illiesia, 2012)
Two new stonefly species, Anacroneuria pakaraima sp. n. and A. wokomung sp. n., are described from adult male and female specimens collected on Mount Wokomung, Guyana. The new species are compared to similar ones known from northeastern South America, and a provisional key to male Anacroneuria from Guyana is presented.
Keywords: entomology; Perlidae; Plecoptera; Anacroneuria; Guyana; new species